Meningkatkan Keterampilan Vokasional Menjahit Totebag (Tas Jinjing) Menggunakan Metode Drill ( Latihan) bagi Anak Tunagrahita Ringan Kelas XI di SLB Luak Nan Bungsu: Array - Keci Oktavia; Marlina; Asep Ahmad Sopan dibandingkan (eductum: Jurnal Literasi Pendidikan, 2023)
This classroom action research was carried out by applying the drill method to improve the vocational skills of sewing totebags for mild mentally retarded children in class XI at SLB Luak Nan Bungsu. Based on the results of the study, it can be concluded that improving the vocational skills of sewing totebags for mild mentally retarded children in class XI is suitable/effective using the drill method (practice). Judging from the results of the implementation of making shell decorations that are done by children, it is increasing from the giving of the first cycle to the second cycle. From the results obtained the initial ability of children from U 35% and O 28% then given action in the first cycle increased to U 64% and O 55% then continued in the second cycle the child's ability increased to U 82% and O 79%. In the implementation of the drill method, it can be developed with various forms and creations that are owned by the teacher which of course adapts to the characteristics of the child. Skills learning activities carried out using tools such as sewing machines, sewing threads, sewing chalk, pencils, scissors, tape measure, rulers and pins, there are also materials in the form of canvas and paper and the learning methods used are able to generate motivation and enthusiasm for children to take part in learning. which has been designed because the child feels trained continuously. The use of the drill method (practice) is carried out continuously in stages. With the hope that the teaching and learning process and results are successful in accordance with the design and learning objectives of vocational skills to sew totebags (tote bags). From the results of the research, after using the drill method, it can improve the vocational skills of sewing totebags for mild mentally retarded children in class XI at SLB Luak Nan Bungsu.